Cavovarus Reconstruction Using a Lateralizing Calcaneal Osteotomy Via Medial Approach. Issue 3 (11th September 2017) - Jaffe, David; Kane, Justin; Royer, Christian; Vier, David
Category: Hindfoot Introduction/Purpose: Calcaneal osteotomies are commonly used to correct a varus hindfoot alignment in a patient with symptomatic cavovarus deformity. Lateralizing osteotomies (i.e. translational, closing wedge, and Malerba) have been implicated in injury to branches of the tibial nerve. The incidence of neurologic deficit after lateralizing osteotomy was recently reported at 34%. These injuries may be due to decreased volume of the tarsal tunnel, but is also postulated that the tibial nerve may be subject to direct or percussive injury when creating an osteotomy from a lateral approach. The hypothesis of this study was there would be minimal clinically significant injury to the tibial nerve by performing the osteotomy from a medial approach and that adequate correction could still be obtained. Methods: A retrospective review of consecutive patients undergoing cavovarus reconstruction by a single fellowship trained foot and ankle surgeon were identified by CPT search from a billing database over a five-year period. Patients were included if they underwent a lateralizing calcaneal osteotomy via medial approach and excluded if a lateral approach was used. Patient demographics, operative reports, and postoperative clinic notes were collected. Presence of immediate postoperative tarsal tunnel syndrome, concomitant procedures performed, perioperative complications, and preoperative and postoperative neurologic examinations were reviewed. Postoperative radiographs were reviewed for location of the osteotomy relative to the posterior tubercle. Results: 24 patients underwent lateralizing calcaneus osteotomy via medial approach. 83.3% of the osteotomies were performed in the middle third of the calcaneus with a mean translation of 11.6 cm. No patients developed acute tarsal tunnel syndrome in the immediate postoperative period. No patients had a documented permanent postoperative tibial nerve palsy. One patient had late onset of lateral foot numbness that resolved by 12 months postoperatively. Another patient noted diffuse numbness of the entire foot. Neither patient reported functional limitations related to these deficits. Other complications included two incision-related complications (8.3%) that required irrigation and debridement, antibiotics, and plastic surgery closure. Three patients underwent removal of symptomatic calcaneal hardware (12.5%). One patient (4.2%) had delayed union of the osteotomy and broke the calcaneus screw. Conclusion: Lateralizing calcaneal osteotomy performed via medial approach has a clinically negligible incidence of neurologic injury and allows for powerful correction of hindfoot varus deformity. Utilizing a medial approach decreases risk of nerve transection and provides less percussive force to branches of the tibial nerve. This technique represents an operative strategy to minimize risk to the tibial nerve and reduce neurologic deficit while providing a powerful translational correction of the hindfoot during cavovarus reconstruction.